2017
DOI: 10.12968/bjon.2017.26.16.s26
|View full text |Cite
|
Sign up to set email alerts
|

Biosimilar monoclonal antibodies (mAbs) in oncology

Abstract: Biological medicines are derived from living cells and organisms. Monoclonal antibodies (mAbs) are biological agents that are widely used to treat malignancies including non-Hodgkin's lymphomas and chronic lymphocytic leukaemia. They are effective but expensive. The patents for many mAbs are expiring, so biosimilar medicines, which contain a version of the active ingredient of the original drug, are being developed. Biological medicines cannot be assessed in the same way as standard generic medications because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In addition, the indications and dose used were the same as those for rituximab. 11,12 A recent multicenter study of systemic sclerosis showed that CT-P10 caused only transient neutropenia and was similar to rituximab in efficacy and other safety profiles. 13 Biosimilars are biological products that contain the active substance of an already authorized original product.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the indications and dose used were the same as those for rituximab. 11,12 A recent multicenter study of systemic sclerosis showed that CT-P10 caused only transient neutropenia and was similar to rituximab in efficacy and other safety profiles. 13 Biosimilars are biological products that contain the active substance of an already authorized original product.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the recent success (and future potential) of CAR-T/TCR-T therapies for the treatment of cancer, we aim to provide a comprehensive overview of the growth of the clinical trials space for these products, and to highlight some of the factors driving this growth. One such factor is the nature of CAR-T/TCR-T immunotherapies, which makes it possible to develop many different products that use analogous therapeutic approach to achieve comparable clinical efficacy [15,16]. Such CAR-T/TCR-T products that are currently in the clinical pipeline cannot be characterized as biosimilar products in the narrow sense of the term, so we propose that CAR-T/TCR-T products that use a parallel therapeutic approach be termed bioparallels.…”
Section: Introductionmentioning
confidence: 99%
“…clinical trials space for these products, and to highlight some of the factors driving this growth. One such factor is the nature of CAR-T/TCR immunotherapies which makes it possible to develop many different products that use analogous therapeutic approach to achieve comparable clinical efficacy [7,8]. Such CAR-T/TCR products that are currently in the clinical pipeline cannot be characterized as biosimilar products in the narrow sense of the term, so we propose that CAR-T/TCR products that use a parallel therapeutic approach be termed bioparallels.…”
Section: Introductionmentioning
confidence: 99%